UPAYA PEMERINTAH DALAM MENANGANI BENCANA ALAM TANAH LONGSOR Studi Kasus di Desa Cihanjuang Kecamatan Cimanggung Kabupaten Sumedang - Dinda Farras Haniya (Magister Administrasi Publik, FISIP, 2021)
Indonesia is famous for its areas that are prone to landslides. For example, in Cihanjuang Village, Cimanggung District, Sumedang Regency, which in early 2021 had experienced a serious landslide disaster. This landslide phenomenon requires an in-depth study so that the arrangement and management is carried out appropriately, where the role of the government here is very large to be able to take the right policy on this problem. Thus, the purpose of this paper is to determine the cause of the landslide disaster and to identify and analyze the government's efforts in dealing with the landslide disaster. This paper uses descriptive qualitative research methods using data derived from secondary data. Based on the results, it was found that the landslide that occurred in Cihanjuang Village was caused by high rainfall, steep slopes, poor drainage system and lack of vegetation. However, the government already has several efforts to be undertaken, including long-term, short-term post-disaster and mitigation. Based on the analysis that has been made, the recommendations for this problem are increasing awareness and socialization for the community, increasing mitigation and monitoring the policy that have been made.